Building Customer Loyalty through Service Quality and Satisfaction: A Study at PDAM KCP Sei Agul - Pika Dea Krismalem; Dianty Putri Purba; Rebecca Evadine (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to assess how the variables of Service Quality and Customer Satisfaction influence Customer Loyalty at PDAM KCP Sei Agul. The research method used is a quantitative approach by distributing online questionnaires to 30 respondents who served as the sample for this study. Data were analyzed using SPSS version 25 with a multiple linear regression approach. The results of the study indicate that both Service Quality and Customer Satisfaction variables have a partial effect on Customer Loyalty. However, these variables do not have a simultaneous effect on Customer Loyalty.